Primary Sexual Abuse Prevention in School Age Children: A Systematic Review - Siti Riskika; Leni Agustin; Nessy Anggun Primasari (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: Sexual Abuse is a condition that needs to be considered in recent years. Sexual abusehas become a public health issue because of the various health effects it causes. So it is necessary to make primary prevention efforts on behaviorsexual abuse, specifically for school age children. The purpose of this study is to find out how effective health education as a primary prevention effort for sexual abuse in school-age children. Method: his papers uses a systematic review design. Data was taken from the ProQuest, Scopus, and ScienceDirect databases with the period 2000-2018. Search was carried out for journals, articles and literature review using keywords of sexual abuse, prevention and psychoeducation. Result: The results of the analysis looked for articles, analysis of 19 articles ppropriates and assessed. namely health education as a form of preventive efforts to prevent sexual abuse in the form of games. The results of the study show that health education wasffort to prevent sexual abuse that occurs a lot in the school and family, health education rovided to school-age children can reduce the occurrence of sexual abuse. Conclusion: Health education is provided in the form of games so that it is easily understood by school-age children.